Evaluating regional water security through a freshwater ecosystem service flow model: A case study in Beijing-Tianjian-Hebei region, China. (October 2017) - Li, Delong; Wu, Shuyao; Liu, Laibao; Liang, Ze; Li, Shuangcheng
Graphical abstract: Highlights: A freshwater ecosystem service flow model were developed to applied in the most severe water scarcity region in china. An obvious mismatch exists between freshwater provision and consumption in the BTH region. Most areas of the Beijing-Tianjin-Hebei (BTH) region, China (69.2%) were affected by upstream freshwater flows. Our Freshwater ecosystem service flow model results can partly serve as the basis for ecological compensation standards among different regions. Abstract: Freshwater ecosystem service is essential to human's survival and development. Many studies have documented the spatial differences in the supply and demand of ecosystem services and proposed the concept of ecosystem services flows. However, few studies characterize freshwater ecosystem service flow quantitatively. Therefore, our paper aims to quantify the effects of freshwater ecosystem service flow on downstream areas. We developed a freshwater ecosystem service flow model and applied it in the Beijing–Tianjin–Hebei (BTH) region, China, for the year of 2000, 2005, and 2010. We assessed the regional water security with an improved freshwater security index by integrating freshwater service provision, consumption and flow; and found that most areas of the BTH region (69.2%) were affected by upstream freshwater flows. The areas achieving water security in the region also expanded to 66.9%, 66.1%, and 71.3%, which were 6.4%, 6.8% and 5.7% increments compared to no-flow situation, in 2000, 2005 and 2010, respectively. Setting quota for human water consumption is suggested to further improve water security. These results highlight the need to fully understand the connections between distant freshwater ecosystem service provision and local freshwater ecosystem service consumption. This approach may also help managers to choose more sustainable strategies for critical freshwater resource management across different regions.